Personality and coping with a low-control situation: The mediating role of cognitive appraisals - Buško, Vesna; Kulenović, Alija (2003)
The study deals with the hypothesized mediating effects of cognitive appraisals on stressfulness of the event in the personality, stress, and coping processes. The relationships between personality measured by NEO-FFI questionnaire, perceived stressfulness of the event, and situation-specific coping measures, were analyzed in a prospective framework with 421 basic military trainees. Analyses of linear structural models partially supported the hypotheses of Lazarus transactional theory on the central mediating role of cognitive appraisal of stress intensity in the relationships between stable antecedents and the ways of coping. Mediating effects of perceived event stressfulness were fully demonstrated for the measure of ‘ emotion-focused coping’ at the beginning of basic training, whereas the latent coping factor of the ‘ acceptance of situation’ proved to be practically independent of the appraised stressfulness. Structural equation models including latent change stress appraisals and coping variables seem to offer more clear interpretation of direct and indirect relations among personality and coping measures found in this study.
Projekt MZOS
ENG